Implementation of Village Fund Allocation Policy In Indonesia - Waris, Irwan (Green Publisher Indonesia, 2022)
This study aims to determine and describe the Implementation of Loli Channel Village Fund Allocation, Banawa District, Donggala Regency, Central Sulawesi Province, Indonesia. The type of research conducted is descriptive qualitative. The informants in this study revealed 5 people. ensure that informants are carried out using a purposive method. This type of data uses primary and secondary data. The data analysis used is Miles and Huberman, namely data reduction, data presentation, and conclusion. The theory used is Edward III's theory which consists of 4 (four) aspects, namely: Communication, resources, attitudes, and employee structure. Based on the research results, show that first, from the aspect of communication it has not been running effectively, where the delivery of communication has not gone well. Second, from the aspect of resources, it has not been supported by adequate human resources in terms of work quality, as well is a lack of technical understanding of the implementing apparatus regarding Village Fund Allocation. Third, in the Disposition aspect, there are still some things that are not appropriate and have not been running properly. Fourth, from the aspect of the bureaucratic structure, there is no standard operating procedure (SOP) regarding the management process and accountability for Village Fund Allocation. Thus, the researcher concludes that the implementation of the Loli Channel Village Fund Allocation policy, Banawa District, Donggala Regency has not run as expected.